Frequency of Calreticulin Genotype among JAK2V617F-negative Patients Suspected with Essential Thrombocythemia - Mushtaq M. Khazeem; Alaa Fadhil Alwan (Journal of Applied Hematology)
BACKGROUND: Myeloproliferative neoplasms (MPNs) without Break Point Cluster- Abelson (BCR-ABL) are mainly divided into three major types: polycythemia vera, essential thrombocythemia (ET), and primary myelofibrosis (PMF). JAK2V617F-negative patients with features of MPN may need to be considered for further evaluation to exclude ET diagnosis. A large proportion of JAK2V617F-negative ET and PMF patients have been shown to have mutations at calreticulin (CALR) gene. These mutations are mutually exclusive with JAK2V617F as proposed. The aim of this study was to retrospectively screen for CALR mutations in JAK2V617F-negative ET suspected patients to evaluate the clinical utility of the test in this population. PATIENTS, MATERIALS, AND METHODS: This retrospective study was performed at the National Center of Hematology/Mustansiriyah University/Baghdad. Initial screening for JAK2V617F was performed using an allele-specific polymerase chain reaction (AS-PCR) procedure. For CALR screening, amplicon length differentiation assay (PCR-amplicon length differentiation assay [ALDA]) method was used. RESULTS: The total number of JAK2V617F-negative cases included in the analysis was 86 cases. Among those, CALR mutations were detected in nine patients (9/86 = 10.47%); 2 cases with CALR Type 1, 6 cases with CALR Type 2, and one case has both types. Out of nine, three cases initially considered secondary conditions were retrospectively diagnosed with ET. Generally, CALR-positive patients were older compared with the CALR-negative group and showed high platelet (PLT) count (P = 0.0011). No significant difference was seen for other blood parameters. CONCLUSION: Screening for CALR mutations in Janus kinase 2-negative patients suspected with ET or PMF could lead to the diagnosis of new cases especially those with high PLT count accompanied by normal values of other blood parameters.